SS-31 modification alleviates ferroptosis induced by superparamagnetic iron oxide nanoparticles in hypoxia/reoxygenation cardiomyocytes - Qizheng Lu; Xiaobo Yao; Hao Zheng; Jinbo Ou; Jieyun You; Qi Zhang; Wei Guo; Jing Xu; Li Geng; Qinghua Liu; Ning Pei; Yongyong Gong; et al. (Heliyon)
Superparamagnetic iron oxide nanoparticles (SPION) are widely used in cardiovascular applications. However, their potential to induce ferroptosis in myocardial cells post-ischemia-reperfusion hinders clinical adoption. We investigated the mechanisms behind SPION-induced cytotoxicity in myocardial cells and explored whether co-loading SPION with SS-31 (a kind of mitochondrial-targeted antioxidant peptide) could counteract this toxicity.To create SPION@SS-31, SS-31 was physically adsorbed onto SPION. To study the dose- and time-dependent cytotoxic effects and assess the influence of SS-31 on reducing SPION-induced damage, hypoxia/reoxygenation(H/R) H9C2 cells were treated with either SPION or SPION@SS-31. We examined the relationship between SPION and ferroptosis by measuring mitochondrial ROS, mitochondrial membrane potential (MMP), lipid peroxidation products, ATP, GSH, GPX4, mitochondrial structure, nonheme iron content, cellular iron regulation, and typical ferroptosis markers.The findings showed that SPION induced concentration- and time-dependent toxicity, marked by a significant cell viability loss and an increase in LDH levels. In contrast, SPION@SS-31 produced results comparable to the H/R group, implying that SS-31 can notably reduce cell damage induced by SPION. SPION disrupted cellular iron homeostasis, with FtH and FtMt expression increased and reduced levels of FPN1 and ABCB8, which led to the overload of mitochondrial iron. This iron dysregulation damaged mitochondrial function and integrity, causing ATP depletion, MMP loss, and decreased GPX4 and GSH levels, accompanied by a burst of mitochondrial lipid peroxidation, ultimately resulting in ferroptosis in H/R cardiomyocytes. Notably, SS-31 significantly alleviated SPION-induced ferroptosis by decreasing mitochondrial MDA production and maintaining GSH and GPX4 levels, indicating its possibility to reverse SPION-induced cytotoxicity. The viability of H/R cells and cells treated with SPION and Fer-1 did not differ statistically, whereas cells exposed to SPION along with inhibitors like 3-MA, zVAD, or Nec-1 showed a substantial loss in viability, implying that ferroptosis is the primary mechanism behind SPION-induced myocardial toxicity.SPION triggers mitochondrial lipid peroxidation by causing overload of iron, leading to ferroptosis in H/R H9C2 cells. Mitochondria appear to be the primary target of SPION-induced toxic effects. SS-31 demonstrates potential in inhibiting this ferroptosis by acting as a mitochondria-targeted antioxidant, suggesting that the modification of mitochondria-targeted antioxidant peptides represents an innovative and practical approach to attenuate the myocardial toxicity associated with SPION.